Deletion of Methionine Sulfoxide Reductase A Does Not Affect Atherothrombosis but Promotes Neointimal Hyperplasia and Extracellular Signal-Regulated Kinase 1/2 Signaling. Issue 12 (December 2015) - Klutho, Paula J.; Pennington, Steven M.; Scott, Jason A.; Wilson, Katina M.; Gu, Sean X.; Doddapattar, Prakash; Xie, Litao; Venema, Ashlee N.; Zhu, Linda J.; Chauhan, Anil K.; Lentz, Steven R.; Grumbach, Isabella M.
Abstract : Objective—: Emerging evidence suggests that methionine oxidation can directly affect protein function and may be linked to cardiovascular disease. The objective of this study was to define the role of the methionine sulfoxide reductase A (MsrA) in models of vascular disease and identify its signaling pathways. Approach and Results—: MsrA was readily identified in all layers of the vascular wall in human and murine arteries. Deletion of the MsrA gene did not affect atherosclerotic lesion area in apolipoprotein E–deficient mice and had no significant effect on susceptibility to experimental thrombosis after photochemical injury. In contrast, the neointimal area after vascular injury caused by complete ligation of the common carotid artery was significantly greater in MsrA-deficient than in control mice. In aortic vascular smooth muscle cells lacking MsrA, cell proliferation was significantly increased because of accelerated G1 /S transition. In parallel, cyclin D1 protein and cdk4/cyclin D1 complex formation and activity were increased in MsrA-deficient vascular smooth muscle cell, leading to enhanced retinoblastoma protein phosphorylation and transcription of E2F. Finally, MsrA-deficient vascular smooth muscle cell exhibited greater activation of extracellular signal-regulated kinase 1/2 that was caused by increased activity of the Ras/Raf/mitogen-activated protein kinase signaling pathway. Conclusions—: Our findings implicate MsrA as a negative regulator of vascular smooth muscle cell proliferation and neointimal hyperplasia after vascular injury through control of the Ras/Raf/mitogen-activated protein kinase kinase/extracellular signal-regulated kinase 1/2 signaling pathway. Abstract : Supplemental Digital Content is available in the text.